Comparison of Brain Transcriptome of the Greater Horseshoe Bats (Rhinolophus ferrumequinum) in Active and Torpid Episodes - Lei, Ming (Public Library of Science, 2014)
Hibernation is an energy-saving strategy which is widely adopted by heterothermic mammals to survive in the harsh environment. The greater horseshoe bat (Rhinolophus ferrumequinum) can hibernate for a long period in the hibernation season. However, the global gene expression changes between hibernation and non-hibernation season in the greater horseshoe bat remain largely unknown. We herein reported a comprehensive survey of differential gene expression in the brain between winter hibernating and summer active greater horseshoe bats using next-generation sequencing technology. A total of 90,314,174 reads were generated and we identified 1,573 differentially expressed genes between active and torpid states. Interestingly, we found that differentially expressed genes are over-represented in some GO categories (such as metabolic suppression, cellular stress responses and oxidative stress), which suggests neuroprotective strategies might play an important role in hibernation control mechanisms. Our results determined to what extent the brain tissue of the greater horseshoe bats differ in gene expression between summer active and winter hibernating states and provided comprehensive insights into the adaptive mechanisms of bat hibernation.